Pengembangan Kerangka Konseptual Risiko Migrasi Hybrid Cloud Computing: Tinjauan Literatur Naratif Perspektif Sistem Informasi - Trinata, Cakra; Fathya, Vita Nurul; Hartati, Besse; Febrianto, Arief; Wibowo, Pascalis Danny Kristi (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Migration to hybrid cloud computing is increasingly being implemented by organizations to achieve a balance between flexibility, security, and cost efficiency in supporting digital transformation. However, integration across private and public cloud environments and the use of multi-cloud environments creates technical and socio-technical complexities that increase operational risks. This study aims to develop a conceptual framework for hybrid cloud migration risks from an Information Systems perspective. The research method uses a narrative literature review of 23 relevant scientific articles. The analysis process is carried out in two stages: grouping literature findings into operational risk domains and mapping risks using Threat, Vulnerability, Risk Factors, Impact, and Damage components. The results identify eight key risk domains, including information security and privacy, compliance and regulation, migration costs, downtime and service availability, existing system integration and compatibility, interoperability and lock-in risk, observability and cross-cloud monitoring, and socio-technical readiness and information technology governance. The resulting conceptual framework emphasizes the importance of integrated risk management through a combination of technical controls and governance mechanisms. Practically, this framework can be utilized to help organizations identify, prioritize, and mitigate hybrid cloud migration risks more systematically.